Nested multiplex PCR for detection of bacterial and fungal blood stream infections in patients with hematological malignancies - Nesma Abdel Aziz Hamdi Hassanin; Nermeen Mahmoud Ahmed Abdallah; Nour Elhoda Hussein Abdalla; Laila Kholeif; Marwa Shabban (Journal of Infection in Developing Countries)
Introduction: Bloodstream Infections (BSIs) are a main cause of life-threatening complications among patients with cancer.